(untitled) (International Journal on Stereo & Immersive Media, 2019)
Many agree that the best-known image related to virtual reality (VR) experiences is the head mounted display (HMD). While the history of headset-mediated virtual reality dates back to the sixties with Ivan Sutherland’s Sword of Damocles trials, the past two years have seen the release of impressive high definition image rendering HMDs that have also prompted the production of various VR experiences such as movies, games, therapeutic content, documentaries and even simple interactive movies just to name a few. The cinematic films had no prior precedent for this medium. Can we truly name VR films cinematic? What can we say about the difference between 360-degree fictional movies and VR computer-generated ones? What can we say about these new categories of technologically-mediated fiction and their spectators? How are they different from the two-dimensional spectator experience? These are legitimate questions that I will address in my paper.